1988
DOI: 10.1063/1.867005
|View full text |Cite
|
Sign up to set email alerts
|

The effects of inertia and interfacial shear on film flow on a rotating disk

Abstract: In this paper the issue is addressed of how a liquid film of uniform thickness thins on a rotating disk because of the action of centrifugal force. The Navier–Stokes equations in self-similar form are solved numerically by a finite-difference method. The effects of film inertia, disk acceleration protocols, and interfacial shear are studied. The numerical results show that inertia has a marked influence on the rate of thinning when the Reynolds number is large and that existing asymptotic theories are inadequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 9 publications
3
38
0
1
Order By: Relevance
“…5(a) shows the axial velocities V RBD and V SE , which continuously decrease until a minimum is reached, and then they increase to zero in around two thirds of the time needed for the film to dry. This is in agreement with previous work, 6 where the modeling of the vertical velocity showed a rapid acceleration followed by a gradual deceleration. (The velocities in Fig.…”
Section: A Thinning Of a Solute-free Liquidsupporting
confidence: 83%
See 2 more Smart Citations
“…5(a) shows the axial velocities V RBD and V SE , which continuously decrease until a minimum is reached, and then they increase to zero in around two thirds of the time needed for the film to dry. This is in agreement with previous work, 6 where the modeling of the vertical velocity showed a rapid acceleration followed by a gradual deceleration. (The velocities in Fig.…”
Section: A Thinning Of a Solute-free Liquidsupporting
confidence: 83%
“…The discrepancy between the Meyerhofer model and the experimental data is due to the Meyerhofer model not accounting for the initial acceleration of the fluid and therefore overestimating the radial outflow, as has been reported elsewhere. 6 In accordance with the improvement of the fits observed for thickness profiles with the RBD model in the presence of vapor, V SE and V RBD are indistinguishable at the highest partial pressure measured (Fig. 5(a)).…”
Section: A Thinning Of a Solute-free Liquidsupporting
confidence: 72%
See 1 more Smart Citation
“…The value of Prandtl number Pr % 6:8 for the base liquid water is obtained using the definition of Prandtl number and thermophysical properties of water (see , Table 1) along with l f ¼ 1 Â 10 À3 Pa s at 20 C. The results presented in Figs. 4,5,6,7,8,9,10,11,12 are based on the thermal conductivity model predicted by the Maxwell [46] and in rest of the figures we have considered the effective thermal conductivity model given by Yu and Choi [47]. Figure 4 shows variation of the film thickness H with time t for different values of the nanoparticle volume fraction /.…”
Section: Resultsmentioning
confidence: 99%
“…The full Navier-Stoke equations for unsteady film development was first considered by Higgins [9] to study the flow problem from the initial stage of film development through the match asymptotic analysis. Later, Rehg and Higgins [10] obtained the numerical solution of transient film flow on a rotating disk for large value of Reynolds number and different spin-up protocols. Dandapat and Ray [11,12] investigated the effects of heating/cooling on thin liquid film development over a rotating disk in presence of the thermocapillarity at the free surface and found that the film thins faster due to thermocapillary effect for the cooling of the disk.…”
Section: Introductionmentioning
confidence: 99%